2018
DOI: 10.1111/cen.13593
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients with nonsurgical hypoparathyroidism and pseudohypoparathyroidism

Abstract: QoL is impaired equally among patients with Ns-HypoPT and PHP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
(75 reference statements)
1
26
0
3
Order By: Relevance
“…In recent years, the burden of illness in HP has been clearly demonstrated . In addition to reduced health‐related quality of life and self‐reported symptoms including fatigue, paraesthesia, brain fog and memory loss , the studies have also shown increased risk of kidney failure, infections and psychiatric disorders . In accordance with these studies, we found that a large proportion of HP patients have been hospitalized due to a crisis, most commonly due to hypocalcaemia, whilst hospitalizations for acute hypercalcemia are relatively rare.…”
Section: Discussionsupporting
confidence: 80%
“…In recent years, the burden of illness in HP has been clearly demonstrated . In addition to reduced health‐related quality of life and self‐reported symptoms including fatigue, paraesthesia, brain fog and memory loss , the studies have also shown increased risk of kidney failure, infections and psychiatric disorders . In accordance with these studies, we found that a large proportion of HP patients have been hospitalized due to a crisis, most commonly due to hypocalcaemia, whilst hospitalizations for acute hypercalcemia are relatively rare.…”
Section: Discussionsupporting
confidence: 80%
“…Complaints of paraesthesia and/or cramps in the past month were present in 3 out of 20 cases. Well-being was not being assessed in this study, but previous data showed failure to restore well-being in patients with HP with standard therapy of calcium and vitamin D (18,19). Therapy with rhPTH 1-84 may help to improve the quality of life in these patients (20).…”
Section: Discussionmentioning
confidence: 86%
“…From a therapeutic aspect, HypoPT is the last endocrine deficiency syndrome not replaced by the lacking hormone in standard care (7, 66). The indirect standard treatment or an un-physiologic substitution therapy might give challenges affecting quality of life (QoL) for the patients but also potential long-term complications (6, 67, 68, 69, 70, 71).…”
Section: Chronic Hypoparathyroidism In Adultsmentioning
confidence: 99%
“…In a number of chronic diseases, quality of life (QoL) of the patients is supposed to be a hallmark of therapy (86, 87, 88) and is regarded as essential also for HypoPT patients by the ESE evidence-based guideline (7). Several instruments for the characterization of QoL in HypoPT patients were used, including the Short Form-36 (SF-36), the Hospital Anxiety and Depression Scale (HADS) and the WHO-5 Well-Being Index survey (WHO-5) (6, 68, 70, 71, 85). These different questionnaires revealed large deviations from the norms observed in the general population (6, 68, 85).…”
Section: Chronic Hypoparathyroidism In Adultsmentioning
confidence: 99%